Toward a New Model of Economic Growth: Synthesizing Stability, Innovation, and Equity - Sesario, Revi (PT. Anagata Sembagi Education, 2026)
Economic growth has long been regarded as a central objective of development policy, yet conventional growth models that emphasize capital accumulation and labor expansion increasingly face criticism for their inability to address environmental degradation, economic inequality, and structural transformation in modern economies. These limitations highlight the need for a new economic growth framework that integrates innovation, institutional stability, inclusiveness, and sustainability. This study aims to analyze the conceptual foundations of a new growth model that synthesizes these dimensions to support balanced and resilient economic development. The research employs a qualitative approach based on a systematic literature review of accredited academic journals and relevant scholarly publications. Data were collected from recent empirical and theoretical studies related to economic growth, financial inclusion, innovation, and sustainable development, and analyzed using qualitative content analysis and conceptual synthesis techniques. The findings indicate that innovation, particularly through digital technology and financial innovation, significantly enhances productivity and supports sectoral transformation. Institutional stability and effective governance strengthen the long-term impact of innovation on economic development, while inclusive financial systems expand access to economic opportunities and reduce inequality. Furthermore, sustainability-oriented policies are essential to ensure that economic growth remains environmentally responsible. In conclusion, a multidimensional growth model that integrates innovation, stability, inclusiveness, and sustainability provides a more comprehensive framework for achieving equitable and sustainable economic development.